2023
DOI: 10.1002/anie.202304720
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Water and Deep Eutectic Solvents in Organosodium Chemistry: Chemoselective Nucleophilic Functionalizations in Air

Giuseppe Dilauro,
Cosimo Luccarelli,
Andrea F. Quivelli
et al.

Abstract: Advancing the development of perfecting the use of polar organometallics in bio-inspired solvents, we report on the effective generation in batch of organosodium compounds, by the oxidative addition of a CÀ Cl bond to sodium, a halogen/sodium exchange, or by direct sodiation, when using sodium bricks or neopentylsodium in hexane as sodium sources. C(sp 3 )-, C(sp 2 )-, and C(sp)-hybridized alkyl and (hetero)aryl sodiated species have been chemoselectively trapped (in competition with protonolysis), with a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Thus, using hexane as a solvent, a range of highly reactive C(sp 3 ), C(sp 2 ) and C(sp) bonded organosodiums have been prepared in situ which subsequently undergo electrophilic interception in DES or even in water as the reaction medium (Figure 5). [24] It was initially demonstrated that sodiated anisole could be formed in hexane from the reaction of elemental sodium and 2-chloroanisole. Under their optimal conditions of using 4 equivalents of metallic sodium to form 1.8 equivalents of the sodiated anisole, the formed aryl sodium complex could be quenched with benzaldehyde under vigorous stirring in a DES mixture of 1 : 3 L-proline/glycerol (Pro/Gly) in a 94 % yield.…”
Section: Alkyl and Aryl Sodiummentioning
confidence: 99%
“…Thus, using hexane as a solvent, a range of highly reactive C(sp 3 ), C(sp 2 ) and C(sp) bonded organosodiums have been prepared in situ which subsequently undergo electrophilic interception in DES or even in water as the reaction medium (Figure 5). [24] It was initially demonstrated that sodiated anisole could be formed in hexane from the reaction of elemental sodium and 2-chloroanisole. Under their optimal conditions of using 4 equivalents of metallic sodium to form 1.8 equivalents of the sodiated anisole, the formed aryl sodium complex could be quenched with benzaldehyde under vigorous stirring in a DES mixture of 1 : 3 L-proline/glycerol (Pro/Gly) in a 94 % yield.…”
Section: Alkyl and Aryl Sodiummentioning
confidence: 99%
“…At the beginning of the century, novel environmentally responsible uids known as deep eutectic solvents (DESs) were recognized as promising alternatives to traditional VOCs in several elds of science, such as organic synthesis, 25,26 catalysis, [27][28][29] main group chemistry, [30][31][32] materials chemistry, 33,34 extraction and separation, [35][36][37] crystallography, 38 and also solar technology to stabilize and improve the photovoltaic performance of DSSCs, [39][40][41][42][43][44][45][46][47] due to their low volatility, high thermal stability, nonammability, ease of preparation, low cost, and tunability of their physicochemical properties. Despite these advantages, however, there are still concerns about their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, recent innovations in organometallic synthesis have demonstrated that at variance with conventional wisdom, polar organolithium and Grignard reagents can be used: (i) in air; (ii) in sustainable, protic, non-toxic and non-dried solvents [such as water or deep eutectic solvents (DESs)]; and (iii) at room temperature, thus reducing costs, waste and consumption of energy and fossil resources. 3–5…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, and aside from the sustainable point of view, the use of the aforementioned protic and polar solvents (water 6 and DESs) in polar organometallic chemistry permitted either the discovery of new reactions/mechanistic pathways or the improvement of selectivity, yields or reaction times (in already known reactions) that cannot be replicated using traditional, dry and toxic VOC solvents. 3,4 This has allowed the extension of the use of aerobic/moisture/ambient temperature compatible with RLi/RMgX synthetic protocols to a wide variety of different areas of interest for general chemistry, including (among others) lithium halogen exchange processes, metalation reactions, Pd-catalyzed C–C coupling protocols or anionic polymerizations. 3,4 In this vein, Hevia, Capriati and some of us have previously reported the possibility of promoting the efficient and selective addition of RLi/RMgX reagents to nitriles in water, 4 d glycerol, 7 a and biomass-derived ethereal solvents (cyclopentyl methyl ether, CPME) 7 b or even under neat conditions 7 c (see Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation